1999
DOI: 10.1063/1.125272
|View full text |Cite
|
Sign up to set email alerts
|

Realization of high tunability barium strontium titanate thin films by rf magnetron sputtering

Abstract: TABLE I. Sputtering conditions for BST deposition. Target Ba 0.5 Sr 0.5 TiO 3 Target diameter 3 in. Source to substrate distance 4 in. RF power 90 W Sputtering gas Ar/O 2 ͑sccm͒ Substrate temperature 450-650°C Gas pressure 50 mT Deposition rate 0.4 nm/min

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(137 citation statements)
references
References 14 publications
5
131
0
1
Order By: Relevance
“…1 together with the reported ones for ͑Ba 0.5 Sr 0.5 ͒TiO 3 film. 2 The changes in capacitance between 0 and 900 kV/ cm for SBTi and CBTi films were 7.0% and 6.5%, respectively, while that for ͑Ba 0.5 Sr 0.5 ͒TiO 3 film was 59%. In addition, the dielectric loss was less than 3%, which was also independent of the applied electric field plotted in Fig.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…1 together with the reported ones for ͑Ba 0.5 Sr 0.5 ͒TiO 3 film. 2 The changes in capacitance between 0 and 900 kV/ cm for SBTi and CBTi films were 7.0% and 6.5%, respectively, while that for ͑Ba 0.5 Sr 0.5 ͒TiO 3 film was 59%. In addition, the dielectric loss was less than 3%, which was also independent of the applied electric field plotted in Fig.…”
mentioning
confidence: 93%
“…[1][2][3][4] The size effect in thin film dielectrics has made it difficult to design their performance characteristics. There has therefore been a strong motivation to discover size-effect-free highly insulating dielectric materials with a high dielectric constant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So, the film has high tunability. Padmini et al 17 reported that when a BST film was subjected to tensile stress, a contraction occurred along the c axis leading to an enhancement of the in-plane oriented polar axis. By a converse electrostrictive effect, the in-plane tensile stress reduces the capacitance in the thickness direction of the film.…”
Section: -2mentioning
confidence: 99%
“…TMOs have been grown by a number of techniques such as solvo-thermal synthesis, 11 sol-gel techniques, physical vapor deposition techniques such as radiofrequency (RF) sputtering 13,14 and e-beam evaporation, 15 and chemical vapor deposition (CVD) including metalorganic CVD (MOCVD) 16 and thermal CVD. [17][18][19][20] Synthesis techniques such as hydrothermal or sol-gel deposition are advantageous for low temperature synthesis of nanostructures, but often result in the inclusion of undesired precursor ions or solvent molecules that can have a significant impact on the electrical properties of the TMOs.…”
Section: Introductionmentioning
confidence: 99%